Social Network of “Pasar Kaget” Traders in Bintan Regency - Muhammad Aditya; Nanik Rahmawati; Rahma Syafitri (Faculty of Social and Political Science Universitas Maritim Raja Ali Haji, Indonesia, 2023)
In Bintan Regency, trading is a common daily activity for many people. Among these traders, there is a social phenomenon known as the